Pembelajaran Tari Tradisional Minangkabau: Antara Penguasaan Gerak dan Pemahaman Nilai Budaya di SMP Negeri 1 Koto XI Tarusan - Rita Maryani; Salsa Bila Nakiah; Indrayuda Indrayuda; Jupriani Jupriani (CV. Alim's Publishing, 2026)
Dance education in schools is not only intended to develop students’ psychomotor skills but also serves as a crucial medium for transmitting local cultural values. However, based on preliminary observations conducted at SMP Negeri 1 Koto XI Tarusan, Pesisir Selatan Regency, the learning process of Minangkabau traditional dance is still heavily focused on mastering dance movements rather than understanding the history, philosophy, and cultural values embedded within the dance. This condition causes students to perform the dance properly while lacking an understanding of the symbolic meanings attached to each movement. This study employed a descriptive qualitative approach using observation, interviews, and documentation techniques to describe the implementation of traditional dance learning at the school. The findings indicate that the dominance of practical exercises has resulted in students’ limited cultural understanding, leading to a pedagogical gap. Therefore, a learning process that integrates skills, knowledge, and cultural values in a balanced manner is urgently needed. This study recommends the use of the Contextual Teaching and Learning (CTL) approach and the active involvement of local cultural figures to make dance learning more meaningful and culturally authentic.